A comparative review of design requirements for natural smoke ventilation in hospital buildings - Ab Ghani, Mohd Zaid; Aripin, Srazali (Malaysian Institute Of Planners, 2018)
Smoke is recognized as the main factor of fatality when fire occurred in a building. Thus, smoke management in the building is of paramount importance in order to achieve a tenable indoor environment in the event of fire other than ensuring passive means of escapes to the place of safety. In hospital building, where patients have limited movements, natural smoke ventilation through windows is the most common form of smoke control design. Nevertheless, inappropriate design of natural smoke ventilation through window may result to poor smoke air flow contributing to unwanted toxic gases inhaled by occupants that lead to fatalities in the event of fire. This study aims to analyse the design requirements and specifications of natural smoke ventilation system in buildings by exploring local and other prominent building regulations as well as code of practices around some countries. The study found that smoke ventilation system (natural and mechanical) is usually applied in windowless building, basement and in large open spaces. The natural smoke ventilation system employs smoke vents (gravity vents) located at a higher level in the roof or at the ceiling level. The regulations state that the size of smoke vents for effective natural smoke ventilation is in between 2% to 3% of the floor areas. Most regulations would allow openable windows for smoke ventilation in the event of fire. © 2018 by MIP.